Efficacy of Protein Bait Sprays in Controlling Melon Fruit Fly [Bactrocera Cucurbitae (Coquillett)] in Vegetable Agro-ecosystems: Controlling Melon Fruit Fly using BAIT Sprays in Vegetable-ecosystems - Abro, Zain-Ul-Aabdin; Baloch, Naheed; Khuhro, Niaz Hussain; Akbar, Waseem (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Melon fruit fly [Bactrocera cucurbitae (Coquillett)] is an injurious pest of vegetables and fruits throughout the cosmos. Vegetables are key source of proteins, minerals and vitamins for human nutrition. However, a number of factors, such as Tephritid flies, confine production of vegetables. Among them, B. cucurbitae is most deleterious pests of the vegetables. In the present investigation, conducted at two field locations of district, Hyderabad during 2016, efficacy of various bait sprays was evaluated in controlling Bactrocera cucurbitae (Coquillett) infestation. The field locations were Jeay Shah and Dehli farm and the cucurbit vegetable crops were bottle gourd (Lagenaria siceraria) and bitter gourd (Momordica charantia). For this purpose, three food attractants such as Nu-lure, Protein hydrolysate and Prima were sprayed on one meter square per field area, as spot treatment. Significantly higher reductions in B. cucurbitae infestations (24.80±2.63, 21.20±2.75) were recorded with Protein hydrolysate followed by Nu-lure (27.80±3.26, 24.20±3.57), as compared with untreated plots, at both field locations (P<0.05). Moreover, higher number of pupae were recovered (121.40±13.81, 115.00±14.17) and higher number of flies and trap catches were observed in control (P<0.05). This study established that Protein hydrolysate is an effective food attractant for reducing B. cucurbitae in all the tested cucurbits. Results of the present investigation would be useful in developing a sustainable pest management strategy in the cucurbit agro-ecosystem.